Studi kasus antara kehalalan dan keharaman COD (Cash On Delivery) dalam Islam - Iin, Khofifa Khurin (Maliki Interdisciplinary Journal, 2024)
In the modern economic era, the use of the "Cash On Delivery" (COD) payment method is common and we often hear about it in online transactions, which often causes problems or questions in the field regarding this method. The purpose of this article is to explore the Islamic view of its use. COD in economic transactions. By using qualitative field research methods with an empirical approach. Buying and selling using a contract like this is permissible according to the majority of ulama and not permissible according to the majority of ulama because there is speculation that it is gharar.